Morton’s neuroma or its mimics: Diagnostic yield of magnetic resonance imaging and radiographic markers in patients referred with a clinical suspicion (Annals of Medical Research, 2026)
Aim: To determine the prevalence of Morton’s neuroma (MN) among patients referred with a clinical suspicion of MN, identify alternative diagnoses, and assess whether angular measurements and the Vulcan sign may help differentiate.Materials and Methods: This retrospective study included 265 feet from 244 patients (mean age, 50.7±13.0 years; 75% female) referred for magnetic resonance imaging with a presumptive diagnosis of MN between January 2020 and June 2025. All patients underwent radiography and magnetic resonance imaging. Morphometric parameters, including the hallux valgus angle, intermetatarsal angle, and interphalangeal angle (IPA), were measured according to the affected web space (2/3 or 3/4). The Vulcan sign was documented on radiographs. Statistical comparisons were performed using the Mann–Whitney U, chi-square, and Fisher’s exact tests.Results: MN was diagnosed in 167 feet (63.0%), while alternative diagnoses were in 98 (37.0%). Bursitis (32.8%), hallux valgus (30.9%), adventitial bursitis (24.5%), hallux rigidus (12.5%), and stress reaction (8.3%) were the most frequent mimics. The 3/4 IPA was significantly greater in MN than in non-MN feet (p
Keywords: Morton’s neuroma; Metatarsalgia; Magnetic resonance imaging; Radiography; Diagnostic imaging; Bursitis